Motivasi Partisipasi Siswa dalam Mengikuti Ekstrakurikuler Pencak Silat di SMP Negeri 2 Pungging Mojokerto - Imelia Indriana Devi; Anung Priambodo (Departement of Mathematics Education, 2024)
Physical Motivational involvement is also part of student participation because it plays a very important role in an activity or participation. Student participation in taking part in activities at school and outside school can be shown by their activeness. Program to improve the individual quality of a student participating in extracurricular activities. The aim of the research is to find out how much motivation and participation motivation is most dominant among students in participating in pencak silat extracurricular activities. Researchers used quantitative descriptive research, using a population of 70 extracurricular participants. The instrument comes from a questionnaire adopted from (Gill et al., 1983) and interviews. Researchers used a motivation questionnaire consisting of six statement indicators. Data is taken via Google form which is distributed via the WhatsApp application. After that, the data is processed using SPSS statistics to find out the Mean, Standard Deviation and Percentage. Based on the results of research conducted, a total of 70 extracurricular students had very high participation motivation with an average percentage of 96.13%. Based on the indicator percentage of the 6 indicators, the average percentage is 96.12%, it can be concluded that participation motivation is included in the Very High category. The most dominant motivation for participation is the fitness indicator with a percentage of 98.51%.